ΔPCO2 and ΔPCO2/C(a−cv)O2 Are Not Predictive of Organ Dysfunction After Cardiopulmonary Bypass - Zhang, Sheng; Zheng, Dan; Chu, Xiao-Qiong; Jiang, Yong-Po; Wang, Chun-Guo; Zhang, Qiao-Min; Qian, Lin-Zhu; Yang, Wei-Ying; Zhang, Wen-Yuan; Tung, Tao-Hsin; Lin, Rong-Hai (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardiac surgery is associated with a substantial risk of major adverse events. Although carbon dioxide (CO2)-derived variables such as venous-to-arterial CO2 difference (△PCO2), and PCO2 gap to arterial–venous O2 content difference ratio (△PCO2/C(a-cv)O2) have been successfully used to predict the prognosis of non-cardiac surgery, their prognostic value after cardiopulmonary bypass (CPB) remains controversial. This hospital-based study explored the relationship between △PCO2, △PCO2/C(a-cv)O2 and organ dysfunction after CPB. Methods: We prospectively enrolled 114 intensive care unit patients after elective cardiac surgery with CPB. Patients were divided into the organ dysfunction group (OI) and non-organ dysfunction group (n-OI) depending on whether organ dysfunction occurred or not at 48 h after CPB. △PCO2 was defined as the difference between central venous and arterial CO2 partial pressure. Results: Forty-eight (42.1%) patients comprised the OI group, of which 25.4% (29/114) had one organ dysfunction, 12.3% (14/114) had two organ dysfunctions, and 4.4% (5/114) had three or more organ dysfunctions. No statistical significance was found (P=0.33) for △PCO2 in the n-OI group at intensive care unit (ICU) admission (10.0, 7.0–11.5 mmHg), and at 4 (9.5, 7.0–11.0mmHg), 8 (9.0, 7.0–11.0 mmHg), and 12 h post admission (9.0, 6.5–11.5 mmHg). In the OI group, △PCO2 also showed the same trend (ICU admission [9.0, 7.0–12.0 mmHg], 4 [9.0, 7.0–11.0 mmHg], 8 [9.0, 8.0–11.0 mmHg] and 12 h [9.0, 8.0–11.0 mmHg], P=0.14). No statistical difference was found for △PCO2/C(a-cv)O2 in the n-OI group (P=0.61) and OI group (P=0.10). No difference was detected in △PCO2,△PCO2/C(a-cv)O2 between groups during the first 12 h after admission (P>0.05). Subgroup analysis of the patients with two or more failing organs compared to the n-OI group showed that the predictive performance of lactate and Base excess (BE) improved, but not of △PCO2 and △PCO2/C(a-cv)O2. Regression analysis showed that the BE at 4 h after admission (Odds ratio=1.28, P=0.004) was a risk factor for organ dysfunction 48 h after CBP. Conclusion △PCO2 and △PCO2/C(a-cv)O2 cannot be used as reliable indicators to predict the occurrence of organ dysfunction at 48 h after CBP due to the pathophysiological process that occurs after CBP.